ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PERKEMBANGAN PERBANKAN SYARIAH DI INDONESIA - Wicaksono, Baghas Budi (Universitas Suryakancana, 2022)
ABSTRAKPerbankan Syariah di Indonesia memiliki perkembangan yang pesat dan signifikan selama 10 tahun terakhir. Hal tersebut diindikasi dengan meningkatnya dana pihak ketiga, penyerapan tenaga kerja di bidang perbankan syariah, serta kontribusi perbankan syariah terhadap produk nasional bruto pada lapangan usaha jasa perbankan. Berbagai indikator makroekonomi diindikasi mempengaruhi perkembangan perbankan syariah di Indonesia seperti suku bunga, cadangan kas wajib, jual/beli surat utang pemerintah, dan indikator makroekonomi lainnya. Adapun penelitian ini dilakukan dengan tujuan untuk mengetahui pengaruh dari variabel indikator moneter dan tenaga kerja terhadap perkembangan perbankan syariah di Indonesia. Peneliti menggunakan pendekatan kuantitatif melalui data sekunder yang diolah dalam model regresi linier berganda. Adapun hasil penelitian menunjukkan bahwa pada persamaan (1) dan (2)Â memiliki hasil bahwa beberapa variabel memiliki pengaruh yang signifikan (p-value > 0,05) dimana tenaga kerja dan suku bunga acuan Bank Indonesia berpengaruh secara dan suku bunga berpengaruh signifikan terhadap perkembangan perbankan syariah di Indonesia. Hal ini mengindikasikan semakin banyak tenaga kerja pada sektor perbankan syariah menyebabkan perbankan syariah semakin berkembang. Sedangkan, suku bunga memiliki pengaruh negatif terhadap perkembangan sektor perbankan syariah. Artinya, ketika suku bunga acuan Bank Indonesia turun, aset perbankan syariah akan meningkat.ABSTRACTIslamic banking in Indonesia has developed rapidly and significantly over the last 10 years. This is indicated by the increase in third-party funds, employment in the sharia banking sector, and the contribution of sharia banking to the gross national product in the banking services business field. Various macroeconomic indicators are indicated to influence the development of Islamic banking in Indonesia, such as interest rates, mandatory cash reserves, buying/selling government bonds, and other macroeconomic indicators. This research was conducted to know the effect of monetary indicator variables and labor on the development of Islamic banking in Indonesia. Researchers used a quantitative approach through secondary data that was processed in multiple linear regression models. The results of the study show that equations (1) and (2) have the result that several variables have aÂ significant influence (p-value > 0.05) where labor and Bank Indonesia's reference interest rate have a significant effect and interest rates have a significant effect on developments. Islamic banking in Indonesia. This indicates that the increasing number of workers in the Islamic banking sector causes Islamic banking to develop. Meanwhile, interest rates negatively influence the development of the Islamic banking sector. This means that Islamic banking assets will increase when Bank Indonesia's benchmark interest rate falls. The appropriate policy recommendations are: (1) The government must be able to maintain monetary economic stability to improve the performance of sharia banking, (2) optimize the performance of state-owned and sharia private banks to increase sharia banking assets, and (3) provide stimulus in the form of appropriate policies in fiscal and monetary matters to the public who use products in the form of sharia banking services.